A Comparison of Determinants of Profitability of China and the UK Commercial Banks - WANG, YING (2019)
Chinese and British banking industries play a pillar role in their national economic development process. Understanding the country's banking system and the decisive factors of bank profitability has become an essential way to understand a country's banking industry. After studying the banking systems of the two countries in detail, this paper adopts the System Generalized Methods of Moments (SGMM) to explore and compare the decisive factors of profitability of China and the UK, which involve the bank internal specific factors and macroeconomic factors. In the bank profitability model, the profitability of commercial banks is expressed as return on average assets ratio (ROAA). Internal factors are closely linked to the size, cost management, liquidity risk management, credit risk management, and capital reserves, while macroeconomic factors are mainly related to GDP growth rate, inflation rate, and unemployment rate. After comparing the decisive factors of bank performance, this paper carries out the Two-Stage Least Square estimator (2SLS) on the instrumental variables employed in the SGMM.